(untitled) - Giles, Will (London, UK, 2000)
Gardeners are moving away from the traditional gardens in favor of vibrant colors, dramatic shapes, and lush plantings. In this celebration of the new, adventurous style of gardening, glorious photographs complement the down-to-earth text. Practical advice, a directory of exotic plants, and instructions on plant care equip readers with the tools they need to integrate subtropical and Mediterranean-style plants in their own temperate gardens.
Keywords: Landscape gardening,Plants, ornamental,Exotic plants